Lymphopenia: A Novel Predictor for Recurrent Cytomegalovirus Disease in Solid Organ Transplant Recipients. (4th October 2017) - Gardiner, Bradley; Nierenberg, Natalie; Chow, Jennifer; Ruthazer, Robin; Kent, David; Snydman, David
Abstract: Background: Twnty to 30% of solid organ transplant recipients (SOTR) treated for cytomegalovirus (CMV) disease will relapse. Identification of risk factors such as extent of disease, degree of immunosuppression, and viral load, as well as an understanding of CMV-specific immune responses, has not impacted relapse rates. We previously demonstrated that a pre-transplant absolute lymphocyte count (ALC) of <1, 000 cells/μL was a predictor of post-transplant CMV disease in liver transplant recipients. We sought to explore the effect of ALC on relapse after treatment for CMV disease. Methods: We performed a retrospective cohort study of SOTR treated for an episode of CMV disease. Our primary outcome was time to first relapse of CMV within 6 months. Data on potential predictors of relapse including ALC were collected at the time of CMV treatment completion. Univariate and multivariate hazard ratios (HR) were calculated with a Cox model. Multiple imputation was used to complete the data. Results: Thirty-three /170 (19.4%) participants relapsed within 6 months. Mean ALC in relapse-free patients was 1.08 ± 0.69 vs. 0.73 ± 0.42 × 10 3 cells/μL in those who relapsed ( P < 0.01, n = 137). Other variables significantly associated with relapse on univariate analysis included older age, later calendar year, living unrelated kidney transplant, use of an antilymphocyte agent within a year, high peak viral load, longer treatment duration and the use of CMV immune globulin. The effect of lower ALC on risk of relapse remained significant even after adjusting for confounders (Table). Conclusion: Lymphopenia at the time of CMV treatment completion was a strong independent predictor for recurrent CMV disease. This is biologically plausible given the known importance of T-cell immunity in maintaining CMV latency. Future studies of recurrent CMV disease in SOTR should consider this inexpensive, readily available marker of host immunity. Disclosures: D. Snydman, Merck: Scientific Advisor, Consulting fee. Shire: Scientific Advisor, Consulting fee